PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP LOYALITAS KARYAWAN (STUDI KASUS DEPARTEMEN PREPARATION PADA KARYAWAN PT PRIMA SEJATI SEJAHTERA BOYOLALI) - Selfinia Utami; Putri Maisara (ITB AAS Indonesia Surakarta, 2023)
This study aims to determine whether transformational leadership style, compensation and work environment significantly affect employee loyalty. The sampling technique was obtained from primary data and secondary data, primary data was obtained by distributing questionnaires using google form to employees of PT Prima Sejati Sejahtera in the Preparation Department for more than 3 years, obtained a number of 73 respondents and the secondary data used was obtained from personnel. In this research method using data instrument test, classical assumption test and hypothesis testing. The data was processed statistically using SPSS. The results showed that there was a significant influence on the variables of transformational leadership style, compensation and work environment on employee loyalty. Keywords: transformational leadership style, compensation and work environment on employee loyalty